2015
DOI: 10.3389/fnbeh.2015.00253
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor serum levels correlate with cognitive performance in Parkinson’s disease patients with mild cognitive impairment

Abstract: Brain-derived neurotrophic factor (BDNF) is a trophic factor regulating cell survival and synaptic plasticity. Recent findings indicate that BDNF could be a potential regulatory factor for cognitive functioning in normal and/or neuropathological conditions. With regard to neurological disorders, recent data suggest that individuals with Parkinson’s disease (PD) may be affected by cognitive deficits and that they have altered BDNF production. Therefore, the hypothesis can be advanced that BDNF levels are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 76 publications
3
40
0
1
Order By: Relevance
“…Serological levels of brain‐derived neurotrophic factor (BDNF), a neuroprotective member of the trophin family, have been linked to PD . With this in mind, we correlated the significantly different metabolites in this study to serological BDNF levels in our cohort, identifying a significant correlations (Pearson's correlation ranges r = 0.33‐0.39) between increased metabolites of FAO and increasing BDNF (Table ).…”
Section: Resultsmentioning
confidence: 95%
“…Serological levels of brain‐derived neurotrophic factor (BDNF), a neuroprotective member of the trophin family, have been linked to PD . With this in mind, we correlated the significantly different metabolites in this study to serological BDNF levels in our cohort, identifying a significant correlations (Pearson's correlation ranges r = 0.33‐0.39) between increased metabolites of FAO and increasing BDNF (Table ).…”
Section: Resultsmentioning
confidence: 95%
“…Evidence suggests that a reduction in BDNF levels and/or function is related to the aforementioned diseases. Notably, the BDNF serum level is positively correlated with the severity of motor symptoms and cognitive impairment in PD patients . Other studies have claimed that BDNF mRNA level is downregulated in the substantia nigra of Parkinsonian syndrome patients .…”
Section: Discussionmentioning
confidence: 97%
“…Notably, the BDNF serum level is positively correlated with the severity of motor symptoms and cognitive impairment in PD patients. 37,38 Other studies have claimed that BDNF mRNA level is downregulated in the substantia nigra of Parkinsonian syndrome patients. 39 These contradictory findings may suggest that the BDNF level is downregulated in the initial phase and upregulated in advanced stages as a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between brain and serum levels of BDNF has not been established; however, several studies suggest that serum levels of BDNF are positively correlative with levels found in brain [5356]. Notably, exercise has been established as an up-regulator of BDNF in both animal and human subjects [14, 5763], as well as in various states of cognitive decline including Alzheimer’s disease [11] for which lowered levels of BDNF have been reported [6467]. Few studies have demonstrated direct positive correlations between exercise-induced BDNF upregulation and improved cognitive function in human subjects (Kimhy D 2015); however, the neuroprotective impact of BDNF upregulation has been well documented [6870].…”
Section: Discussionmentioning
confidence: 99%